A complex DICER1 syndrome phenotype associated with a germline pathogenic variant affecting the RNase IIIa domain of DICER1. Issue 2 (18th November 2020) - Pontén, Emeli; Frisk, Sofia; Taylan, Fulya; Vaz, Raquel; Wessman, Sandra; de Kock, Leanne; Pal, Niklas; Foulkes, William D; Lagerstedt-Robinson, Kristina; Nordgren, Ann
Abstract : Background: Germline pathogenic variants in DICER1 cause DICER1 syndrome, an autosomal dominant, pleiotropic tumour predisposition syndrome with variable expressivity and reduced penetrance for specific dysplastic and neoplastic lesions. Recently, a syndrome with the acronym GLOW ( G lobal developmental delay, L ung cysts, O vergrowth, W ilms tumour) was described in two children with mosaic missense mutations in hotspot residues of the DICER1 RNase IIIb domain. Methods: Whole genome sequencing, exome sequencing, Sanger sequencing, digital PCR and a review of Wilms tumours with DICER1 RNase III domain mutations were performed. Results: A de novo heterozygous c.4031C>T (p.S1344L) variant in the sequence encoding the RNase IIIa domain of DICER1 was detected. Clinical investigations revealed a phenotype that resembles the GLOW subphenotype of DICER1 syndrome. Conclusion: The phenotypic overlap between patients with p.S1344L mutation and GLOW syndrome provide clinical support for recent discoveries that RNase IIIa-Ser1344 site mutations impede miRNA-5p biogenesis analogous to DICER1 hotspot mutations in the RNase IIIb domain. We show that an individual with a heterozygous germline p.S1344L mutation has a severe form of DICER1 syndrome ('DICER1 syndrome plus'), with notable features of intellectual disability, macrocephaly, physical abnormalities, Wilms tumour and a well-differentiated fetal adenocarcinoma of the lung.